TEKNIK PENYEMBUNYIAN PESAN TEKS TERENKRIPSI ALGORITMA MERKLE-HELLMAN KNAPSACK MENGGUNAKAN METODE PIXEL VALUE DIFFERENCING KE DALAM CITRA DIGITAL - Agung Lestari; Abdul Sani Sembiring; Taronisokhi Zebua (STMIK Budi Darma, 2019)
Optimization of data security techniques is very necessary so that the data or information that is secured is really safe from attack. Data that has been encrypted based on cryptographic techniques very quickly raises suspicion that the data is confidential or important. Therefore, this technique is better combined with steganography techniques. Utilization of steganography techniques can minimize the attacker's suspicion of data that is secured, because by using steganography data techniques can be hidden on certain objects. This study discusses how to encode a text based on the Merkle-Hellman Knapsack algorithm and the resulting password is hidden in a grayscale digital image as a hiding object based on the pixel value differencing algorithm. This is done to minimize suspicion and make it difficult for attackers to find out confidential or important data.Keywords: cryptography,steganography, merkle-hellmankanpsack, PVD, image